Mucinous carcinoma of breast: FNAC as effective diagnostic modality - Tyagi, Ruchita; Kumar, Mahendra; Tanwar, Pranay; Dey, Pranab (Asian Journal of Medical Sciences, 2013)
Mucinous carcinoma of the breast in pure form comprises only 2% of all breast cancers. Pure mucinous carcinoma of the breast have better prognosis. They are usually having higher incidence in peri-menopausal and post-menopausal age group. We report a 32-year-old female, clinically suspected to have benign breast disease, diagnosed as mucinous carcinoma of the breast on FNAC. In such cases, there is always a high probability of missing the diagnosis at imaging because of the absence of established radiological signs of malignancy such as calcification and spiculation. In this case imaging was not helpful and diagnosis was ascertained by FNAC. This case further strongly substantiates, Fine needle aspiration cytology as rapid , highly sensitive and highly specific diagnostic investigation of choice for management of breast lumps . Asian Journal of Medical Science, Volume-3 No-3 (2012), Page -32-35 DOI: http://dx.doi.org/10.3126/ajms.v3i3.5240